DOP01 Exclusive enteral nutrition for the treatment of adult Crohn's disease. (15th January 2020) - Shukla, D; Purcell, L; Palmer, M; Pillay, L
Abstract: Background: Crohn's disease (CD) is a debilitating autoimmune disease affecting >40 000 Australians. Exclusive enteral nutrition (EEN) is an effective, risk-free therapy in children with CD, offering an ~80% success rate. Despite similar efficacy in adults, including the potential to decrease the need for high-risk steroids and surgery, adherence remains an unresolved obstacle for its use, with withdrawal rates of up to 40% (Wall 2013). Lack of dietetic expertise and support for adults on EEN were identified as primary barriers (Wall 2013). This prospective, single-centre, observational study aimed to assess the impact of a 6-week EEN model of care on disease symptoms, nutrition and inflammatory markers. We also assessed if >80% of adults with CD could adhere to EEN. Methods: Adults with active CD were treated with oral EEN for six weeks between March 2018 and September 2019 which uniquely included weekly specialist Dietetic support. EEN is the provision of 100% of a patient's nutritional requirements via a nutritionally complete liquid formula. Paired assessment at baseline and EEN completion occurred for Crohn's disease activity index (CDAI), calprotectin, C-reaction protein (CRP), platelets, albumin, white cell count, weight and calprotectin using paired t -tests. The primary outcome measure was disease activity using CDAI. Results: Twenty-seven eligible CD patients were identified. Most patients (85%, n = 23/27) successfully adhered to EEN treatment (45 ± 13 years, 63% female, 52% had Calprotectin ≥100). The patients were further subdivided as per Montreal classification (L1: n = 12; L2: n = 3; L3: n = 12) and 93% were on medications such as steroids ( n = 9/27), immunosuppressives ( n = 19/27) and biologics ( n = 16/27). After EEN, 74% ( n = 20/27) achieved clinical remission (CDAI <150) 19/27 patients (70%) achieved clinical response with >70-point reduction in CDAI score and most (77%) patients achieved greatest improvement in CDAI score in the well-being section. A trend showed that 37% ( p = 0.087) more patients with L2 and L3 CD achieved clinical response through CDAI than L1 CD patients. Calprotectin also showed a trend for improvement (-23(-65230-150) µg, p = 0.067, n = 20). No differences were observed in CRP, white cell count, or albumin ( p = 0.262–0.433, n = 12–13); however, platelets showed a trend for improvement (-26(-156-46) µl, p = 0.071, n = 12) and weight reduced by −2.4(3.2) kg ( p = 0.001). Few (30%, n = 8/27) patients changed medications during EEN treatment. No significant side effects were observed. Conclusion: EEN may be achievable for most adults with additional professional support and has merit in assisting patients with clinical improvement of CD.